Using Molecular Markers for Evaluate the Uniformity among the Awassi Flocks in South Kirkuk Province - Abdulazeez, Sarmad Talib; Abaas, Nibras Majid; Shaker, Ahmed Sami; Ameen, Questan Ali; Hamad, Aram Omer (American Journal of Biology and Natural Sciences, 2025)
The objective of this study was to assess the genetic diversity and population structure of the indigenous Awassi sheep in Southern Kirkuk (North of Iraq). Four flocks were randomly chosen from different geographical regions and 10 rams and 10 ewes were randomly selected in each flock. Five polymorphic microsatellite markers SSR characterised by their high polymorphism in sheep were analysed on blood-derived genomic DNA samples. PCR amplification and genetic analysis were based on established molecular and statistical procedures. The genetic diversity was estimated by diversity indices such as observed (Na) and effective number of alleles (Ne), Nei’s gene diversity (h), Shannon’s index (I), and percentage of polymorphic loci. The results showed that, in both sexes, females showed higher allactic richness (Na = 1.4000), gene diversity (h = 0.1500) and Shannon’s index (I = 0.2249) than males. Ht was twice as large in females (0.1500) compared to males (0.0750), but Hs was equal to zero in both, revealing that genetic Structure was high. The strong genetic differentiation (Gst = 1.0000) and low gene flow (Nm = 0.0000 in females, 1.0000 in males) might indicate reproductive isolation, most likely among the females. A dendrogram based on pairwise genetic identity matrices confirmed this, showing comparatively greater variation among females than among males, which were more homogeneous in their genetic differentiation. Significance These results underline the necessity of sex-influenced genetic manager of conservation purpose and the need of broader genetic repertoire of the genome for maintain genetic diversity not to be lowered in Awassi sheep populations.